EXPLORING THE RELATIONSHIP BETWEEN SELF-EFFICACY AND STRESS IN ELDERLY HYPERTENSION PATIENTS - Budiman, Amin Aji; Prastiwi, Firman; Vierdiana, Dyah; Amrullah, Adhi Wardhana; Rahmad, Muhamad Nur; Rosida, Nikma Alfi (Universitas Kusuma Husada Surakarta, 2025)
Background: Elderly individuals with hypertension often face high stress levels, which can worsen their physical and psychological health. Self-efficacy, the belief in one's ability to manage challenges, plays a crucial role in coping with chronic illness. Research suggests that higher self-efficacy is linked to better stress management and improved health outcomes. In hypertensive elderly, strong self-efficacy may help reduce stress by promoting confidence in handling daily tasks and medical routines. Understanding this relationship is essential for developing effective interventions to support elderly patients and enhance their quality of life. The purpose of this study was to determine the relationship between self-efficacy and stress levels in elderly people with hypertension. Methods: This research design is correlational analytic using a cross-sectional approach; the instruments in this study were the Self-efficacy to Manage Hypertension-Five Item Scale and the Perceived Stress Scale (PSS). The sample in this study consists of 65 respondents, all of whom are elderly individuals diagnosed with hypertensionResults: 12 (18,5%) elderly experienced low self-efficacy, and 5 (7,7%) elderly had severe stress. There is a negative relationship between self-efficacy and stress in the elderly, with a p value <0.000 (<0.05), with a correlation of -.580**. Conclusion: This means that the higher the self-efficacy possessed by the elderly, the lower the stress that arises. Self-efficacy plays an important role in reducing stress in the elderly, especially those who suffer from hypertension. The elderly are recommended to increase their self-efficacy through several complementary therapies.